Systemic risk in a network model of interbank markets with central bank activity - Co-Pierre Georg; Jenny Poschmann (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
The breakdown of the interbank money markets in the face of the recent financial crisis has forced central banks and governments to take extraordinary measures to sustain financial stability. In this paper we investigate which influence central bank activity has on interbank markets. In our model, banks optimize a portfolio of risky investments and riskless excess reserves according to their risk and liquidity preferences. They are linked via interbank loans and face a stochastic supply of household deposits. We then introduce a central bank into the model and show that central bank activity enhances financial stability. We model the default of a large bank and analyse the resulting contagion effects. This is compared to a common shock that hits banks who have invested in similiar assets. Our results indicate that common shocks are not subordinate to contagion effects, but are instead the greater threat to systemic stability.
Keywords: C63; E52; E58; G01; G21; 330; systemic risk; interbank markets; monetary policy; contagion; common shocks; Geldmarkt; Bankrisiko; Schock; Ansteckungseffekt; Bankenkrise; Geldpolitik; Zentralbank; Finanzmarktkrise; Theorie